Running biomechanics in a long-term monitored recreational athlete with a history of Achilles tendon rupture - Jandacka, Daniel (BMJ Publishing Group, 2013)
This study represented a unique opportunity to understand changes in the human motion biomechanics during basic locomotion within a time interval of 4 years, when the monitored individual regained his original aerobic fitness, running performance and body mass index as prior to the injury. The participant visited the laboratory a month prior to the injury and during 4 years after the surgery. The surgery, subsequent rehabilitation and a 4-year running training programme in the studied recreational athlete did not completely eliminate the consequences of the Achilles tendon rupture. The function muscle deficit is namely manifested by a lower net plantar flexion moment and a lower net-generated ankle joint power during the take-off in the stance phase. The greater dorsal flexion in the affected ankle joint at the first contact with the ground and consequently higher peaks of ground reaction forces during running are consequences of the longer Achilles tendon in the affected lower extremity and weakened calf muscles.